Entrepreneurship and Family Role: A Systematic Review of a Growing Research - Cardella, Giuseppina Maria; Hernández-Sánchez, Brizeida Raquel; Sánchez García, José Carlos (Frontiers in Psychology, 2020)
: In recent years, research on the family role and entrepreneurship has increased extremely, consolidating itself as a valid and current subject of study. However, a part of the scientific literature seems to lack systematization and the boundaries appear unclear, maybe due to its multidisciplinary nature. This paper presents a systematic analysis of academic research, applying bibliometric indicators and cluster analysis, which define the state of research on the international scene. For this purpose, using three well accepted databases among the research community: Scopus, Web of Science, Business Source, a total of 92 articles were selected and analyzed, published between 1989 and 2019 (until March). The results show that this is a relatively recent field of study, with a multidisciplinary character and in which the most influential authors do not coincide with the most productive scientific journals. A cluster analysis finds out five main areas of literature development: the cluster with the largest percentage of co-occurrences (25%) is the one that relates to the dimensions of entrepreneurship, self-employment and personality; in contrast, the area with a lower percentage of co-occurrences of keywords (12,1%) is refers to family business, succession, economic development and Arabia Saudita. Based on the outcome obtained and the shortcomings above, in the final part of the article, possible points of reflection for future research are exposed, which could be useful to further of this field of study.